Economic evaluation of vancomycin-resistant enterococci (VRE) control practices: a systematic review. Issue 1 (May 2020) - MacDougall, C.; Johnstone, J.; Prematunge, C.; Adomako, K.; Nadolny, E.; Truong, E.; Saedi, A.; Garber, G.; Sander, B.
Summary: Preventing vancomycin-resistant enterococci (VRE) infection is a healthcare priority. However, the cost-effectiveness of VRE control interventions is unclear. The aim of this study was to synthesize evidence on economic evaluation of VRE control practices such as screening, contact precautions, patient cohorting, and others. The literature was searched from January 1985 to June 2018, and included economic evaluations of VRE control practices in hospital settings, published in English. A total of 4711 articles were screened; nine primary studies met our criteria. All studies evaluated some form of VRE screening and contact precautions, in populations ranging from single hospital wards (or select patient groups) to multiple healthcare facilities. There was significant variability in the interventions and comparisons used. Most studies ( N = 7) conducted a cost-effectiveness analysis; two studies were cost-consequence studies. All economic evaluations were from the hospital perspective. Four studies found implementing enhanced VRE-specific control practices to be cost-effective/cost-saving and two studies found that discontinuing VRE-specific control practices was not cost-effective. Three studies found decreasing VRE-specific control practices to be cost-effective/cost-saving. The quality of the included studies was generally low according to the Joanna Briggs Institute (JBI) checklist for economic evaluations; major limitations included risks of bias in intervention effect estimates, and a lack of sensitivity analyses. Most studies show that some form of VRE screening and use of Contact Precautions is cost-effective. The low study quality and heterogeneity of interventions and comparators precludes definitive conclusions about the cost effectiveness of specific VRE control interventions. Additional high-quality economic evaluations are needed to strengthen the available evidence.